Democracy & the Political in Max Weber's Thought - Maley, Terry (Book collections on Project MUSE., 2011)
Maley critically examines how Weber's realist 'model' of democracy defines and constrains the possibilities for democratic agency in modern liberal-democracies. Maley also looks at how ideas of historical time and memory are constructed in his writings on religion, bureaucracy, and the social sciences. Democracy and the Political in Max Weber's Thought is both an accessible introduction to Weber's political thought and a spirited defense of its continued relevance to debates on democracy."--Pub. desc.